2007
DOI: 10.1093/molehr/gam071
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition and apoptosis induced in human leiomyoma cells by treatment with the PPAR gamma ligand ciglitizone

Abstract: The nuclear receptors PPARs (peroxisome proliferator-activated receptors) are transcription factors that play important roles in multiple disease conditions. The activation of PPARs by specific ligands is associated with growth suppression of several different types of human cancer, but the molecular mechanism responsible for this growth suppressive effect remains elusive. The aim of this study was to determine the distribution of PPARgamma protein/mRNA expression in uterine leiomyomas and to identify the PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Embryos were incubated in 25 µ m PPARG antagonist BADGE[28] or agonist 10 µM Ciglitizone[40] at ∼24 hpf until the desired developmental stage.…”
Section: Methodsmentioning
confidence: 99%
“…Embryos were incubated in 25 µ m PPARG antagonist BADGE[28] or agonist 10 µM Ciglitizone[40] at ∼24 hpf until the desired developmental stage.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, they concluded that PPARγ signaling may lead to inhibition of leiomyoma growth through modulating estrogen signaling. In addition, Nam and colleagues (161) found that leiomyoma cells are more sensitive than myometrium cells to the proliferation-inhibiting effect of ciglitizone, a member of the TZD family of PPARγ ligands. This implies that PPARγ signaling may modulate leiomyoma growth.…”
Section: Peroxisome Proliferator-activated Receptor γmentioning
confidence: 99%
“…This implies that PPARγ signaling may modulate leiomyoma growth. Finally, modulating this signaling pathway through PPARγ ligands may present a potential therapeutic target (161,162).…”
Section: Peroxisome Proliferator-activated Receptor γmentioning
confidence: 99%
“…As a cancer therapy agent, curcumin has molecular function at the transcriptional level (NF-kB, STAT, AP-1, PPAR-g, Egr-1, b-catenin, and Nrf-2 signaling pathways), and has demonstrated efficacy as an inductor of apoptosis in multiple human cancers including skin (45), leukemia (46), colon (47), liver (48), breast (49), lymphoma (50), neuroblastoma (51), pancreatic (52), lung (52), endometrial (53), and ovarian (54). In human leiomyomas, there is evidence of a disruption in apoptosis, resulting in tumor growth (28); and various potential leiomyoma therapies, including gonadotropin-releasing hormone (GnRH) agonists (55), CDB-2914 (56), cetrorelix (57), asoprisnil (58), genestein/TKS050 (59), 2-methoxyestradiol (60), raloxifene (61), and ciglitizone (62), have demonstrated efficacy by regulating apoptosis in leiomyomas. Our results demonstrate that curcumin stimulated a metabolic profile compatible with the induction of apoptosis in human leiomyoma cells.…”
Section: Figurementioning
confidence: 99%